Review on Protection Against Transients and Surges in Power System - Norliza Abd. Razak; Hamadi (International ABEC, 2021)
The most essential issue for electricity providers to address is power distribution breakdowns. A surge is a voltage or current wave that occurs suddenly. It happened within the power system in a very brief period of time, usually a few milliseconds. Furthermore, a surge in the electrical system can be caused by lightning, utility switching, including capacitor switching, equipment switching, and switching inductive loads within a facility. Surge protection systems are widely used around the world. The term "surge protection device" (SPD) refers to devices that protect electronics from surges and transients. We use the term SPD to refer to devices that safeguard systems and equipment from electrical transients in this study. The method for selecting SPD to protect a power system must adhere to the IEC 62305 guideline. The purpose of this article, from the standpoint of the power system, is to review the protection against transient and surge using appropriate methods and adhering to all standards in order to satisfy the requirements.